Potential of Porous Co3O4 Nanorods as Cathode Catalyst for Oxygen Reduction Reaction in Microbial Fuel Cells - Kumar, Ravinder; Singh, Lakhveer; Zularisam, A. W.; Hai, Faisal I. (Elsevier, 2016)
This study aims to investigate the potential of porous Co3O4 nanorods as the cathode catalyst for oxygen reduction reaction (ORR) in aqueous air cathode microbial fuel cells (MFCs). The porous Co3O4 nanorods were synthesized by a facile and cost-effective hydrothermal method. Three different concentrations (0.5 mg/cm2, 1mg/cm2 , and 2 mg/cm2) of Co3O4 nanorods coated on graphite electrodes were used to test its performance in MFCs. The results showed that the addition of porous Co3O4 nanorods enhanced the electrocatalytic activity and ORR kinetics significantly and the overall resistance of the system was greatly reduced. Moreover, the MFC with a higher concentration of the catalyst achieved a maximum power density of 503 ± 16 mW/m2, which was approximately five times higher than the bare graphite electrode. The improved catalytic activity of the cathodes could be due to the porous properties of Co3O4 nanorods that provided the higher number of active sites for oxygen.